Defunct bus companies in Iloilo City, 1945-1968 - Dionela, Romel R.
This paper is a descriptive study of the history of the defunct bus companies operating in Iloilo City from 1945 to 1968. It deals with the origin, areas of operation, expansion and the causes of eventual cessation of operations of these bus companies., The objectives of the study are: 1) to trace the origin of the bus companies operating in Iloilo City from 1945 to 1968; 2) to find out the factors that led to their expansion; 3) to know the reasons behind the eventual cessation of their operations; 4) to describe the characteristics of the buses these companies fielded; 5) to describe the characteristics of the bus industry other than the features of the buses; and 6) to assess the contribution of these bus companies to the development of Iloilo City. The influx of American surplus motor engines and the lack of competition during the early years after the war motivated some to put up bus companies. Also the availability of private funding as well as loans from an American financier, Charles Hodges, led to some private individuals to set up bus transportation business. The lack of competition and the buses' cheaper fare led to the expansion of some bus companies. There were seven bus companies that operated in Iloilo City from 1945 to 1968. They were Serrantes transportation, Palma Transit, L & L Transport, Ven's Battery Station, Star of the South, Anelen Transit and Glory Texas. All of these bus companies fielded units in the Jaro-Iloilo route. Only the Star of the South fielded units to other city routes namely, Jaro-Mandurriao and Molo-Arevalo. The factors that led to the decline of the bus companies were high cost of maintenance and stiff competition with the public utility jeepneys and other bus companies. Some suffered because of the type of management of some bus companies that was centered on the owner alone. Some bus companies did not have an effective control measures to monitor and stop erring employees. Financial losses forced the companies to stop operating. With the cessation of their operations, the jeepneys took over the route all over the city, Since the bus companies practically existed in the same period of time, the units they owned shared many features. The engines used by these buses were American brands : Ford Chevrolet and International. All these engines were using gasoline. The body structures and sizes were mini-buses and medium-sized buses. Mini-buses carried thirty passengers while medium-sized buses can carry fifty passengers. The bus companies provided an easier, safer, faster and cheaper means of transportation. They provided hundreds of employment. The body of the buses were constructed in the city giving more jobs and showed skills and craftsmanship of the people. Employees, students and other people were able to travel easily to their different destinations. The buses helped to carry and deliver forms of printed mass media and made possible for people to visit relatives and friends. The bus companies also helped to bolster the tourism potential of the whole area. tourist found buses readily available for hire to the different sights, colorful festivals and historical sites in the area.